Electrochemical properties of Ebonex®/Pt anodes - Kasian, O. I.; Luk'Yanenko, T. V.; Amadelli, Rossano; Velichenko, A. B. (Russian Journal of Electrochemistry, 2013)
The electrochemical behavior of platinized Ebonex® was studied. The electrochemical and semiconductor properties of electrodes can be varied within wide limits by thermal treatment of Ebonex®/Pt, which selectively affects the electrocatalytic activity of anodes in the oxygen evolution reaction. The reduction peak of platinum oxides on the cyclic voltammetry (CV) curves can be used as a correlation parameter when evaluating the electrocatalytic activity of Ebonex®/Pt electrodes in the oxygen evolution reaction. © 2013 Pleiades Publishing, Ltd.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Ebonex®/Pt; electrocatalytic activity; semiconductor properties